2015
DOI: 10.1002/hrm.21650
|View full text |Cite
|
Sign up to set email alerts
|

Orientation Training and Job Satisfaction: A Sector and Gender Analysis

Abstract: Using data from the British Household Panel Survey (BHPS), we investigate how various types of job training impact upon employees’ job satisfaction and its domains. We find that orientation training exerts a significant positive effect on newcomer male employees’ job satisfaction in both the private and public sectors, but it increases the job satisfaction of newcomer female employees only in the public sector. Other types of job training have only a weak effect on job satisfaction. We attribute the predominan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 63 publications
2
24
0
Order By: Relevance
“…Many studies relating to structured workplace orientation programmes indicate their importance in influencing job satisfaction (Tabvuma, Georgellis, & Lange, ) and safety in the new workplace (Curcuruto, Mearns, & Mariani, ). In our study, we found considerable diversity in the length and content of orientation programmes and other support systems, with a third of our respondents reporting eight hours or less orientation, and nearly half having no supernumerary period.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies relating to structured workplace orientation programmes indicate their importance in influencing job satisfaction (Tabvuma, Georgellis, & Lange, ) and safety in the new workplace (Curcuruto, Mearns, & Mariani, ). In our study, we found considerable diversity in the length and content of orientation programmes and other support systems, with a third of our respondents reporting eight hours or less orientation, and nearly half having no supernumerary period.…”
Section: Discussionmentioning
confidence: 99%
“…The pattern is characterised by a significant increase in the reported level of job satisfaction when individuals enter the new job ('honeymoon') and its subsequent decline back to the baseline over time ('hangover'). Research shows that the honeymoon effect often results from organizations' tendency to portray their most favourable characteristics to new recruits during the hiring and initial socialisation processes (Ashforth, 2001;Van Maanen, 1975;Tabvuma, Georgellis and Lange, 2015) combined with individuals' tendency to rationalise the decisions which they have already made (Lawler, Kuleck, Rhode and Sorensen, 1975;Vroom and Deci, 1971). The hangover effect can be accounted for by socialization theory (Chatman, 1991;Louis, 1980) or set point theory (Headey and Wearing, 1989), both of which suggest that individuals adapt to changes over time as they gain increased information about and exposure to the new environment.…”
Section: Introductionmentioning
confidence: 99%
“…In such a context, predictable, reliable and consistent signals from an employer can be seen as a catalyst to motivate a group identification process, brought about and strengthened by social interactions and a shared understanding of job requirements, which allows uncertainty to be reduced and expectation clarity to be restored. In recent studies, the theory has also been employed to explain uncertainty reduction in the organizational socialization process by gaining information about various aspects of work (Tabvuma et al, 2015).…”
Section: Discussionmentioning
confidence: 99%